Infrastructure as a Catalyst for Regional Integration, Growth, and Economic Convergence: Scenario Analysis for Asia - David Roland-Holst (Asian Development Bank (ADB), 2006)
As Asia's economic growth process matures, regional integration offers important opportunities to sustain and extend the achievements of the more dynamic economies. Benefits from this process will include geographic diversification, often toward superior growth rates, as well as structural differentiation and more rapid evolution from established north–south patterns of trade and specialization. Propagation of growth linkages across this diverse region will also facilitate more inclusive growth and economic convergence. Infrastructure commitments can be an essential guarantor of the entire process, and this paper examines their potential to contribute to more sustained and broadly based Asian growth.
hdl:11540/1888
Keywords: 330; Regionale Wirtschaftsintegration; Infrastrukturinvestition; Transportkosten; Wirtschaftswachstum; Wirtschaftliche Konvergenz; CGE-Modell; Allgemeines Gleichgewicht; Szenariotechnik; Asien